Aircraft carriers : inside and out - Beyer, Mark (Mark T.) (Technology--blueprints of the future, 2002)
Describes the history, design and construction, components, and future of aircraft carriers, and discusses such famous ones as the USS "Saratoga" and "Enterprise.".